Comparative Analysis of Body Composition Before and After Periodic Special Training of Basketball Players - Gong RongRong (Ilmu Inovasi Nusantara, 2024)
With the continuous development of basketball in modern society, body composition is used by more and more sports workers to evaluate the training status of basketball players, and realize that the change of various indicators of body composition after special basketball training has a great impact on the skills and tactics and athletic ability of basketball players.By understanding the structure and proportion of body composition before and after the special training of basketball players, coaches and students can view the change of weight more objectively, conduct more targeted and scientific training, and arrange meals reasonably. The methods in this paper use testing, literature and mathematical statistics, Using South Korea production of biological electrical impedance body composition analyzer as an experimental instrument, in Shanxi normal university level 18 basket designed class two 18 girls as the research object, measure the two months before and after the physical training, training three times a week, a lasting 90 minutes, exercise intensity for moderate intensity, not other special training, special basketball training before and after the test data of related comparative analysis.The results showed that the visceral fat level, body fat rate, waist-hip ratio, body age and total body moisture of basketball students decreased after special training, in which the body fat rate and body age were significantly reduced after training; height did not change; weight, total energy consumption, mineral and basic metabolism increased significantly after training; the protein increased than before training.The special training of basketball is different from the special training of other sports events, so the influence on the indicators of the body composition is also different, and the requirements for the indicators are also different. It is necessary to correctly analyze the changes of each component, and adjust the training and diet accordingly